Adaptability and stability in maize: grain yield vs severity of gray leaf spot - Engelsing, Márcio José; Coimbra, Jefferson Luís Meirelles; Vale, Naime Martins do; Barili, Leire Daiane; Stinghen, Jussara Cristina; Guidolin, Altamir Frederico; Bertoldo, Juliano Garcia (Revista de Ciências Agroveterinárias, 2012)
The environmental adaptability and the stability of corn grain yield is used in genotype recommendation. This work aims to estimate the adaptability and the stability parameters of corn genotypes, using three places (Água Doce, SC, Iraí de Minas, MG e Chapadão do Céu, GO). These parameters were estimated for the character grain yield (kg ha-1) and Gray Leaf Spot (GLS) severity. Twenty corn hybrids were used by crossing five parents (S7) denominated A, B, C, D and E of Agroeste Sementes S.A. The adaptability and the stability parameters were estimated by linear regression as proposed by Eberhart; Russel (1966). The results presented a significant difference among the treatment factors (environment, hybrid and interaction between hybrid and environment). The great majority of tested hybrids presented a wide adaptability and a high phenotypic stability for the grain yield and GLS severity. The evaluation of genotypes 5, 6 and 10 (BxA, BxC and CxB, respectively) must continue in the plant breeding program.